2011
DOI: 10.1186/1475-2875-10-27
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ, a valuable surrogate marker of Plasmodium falciparum pre-erythrocytic stages protective immunity

Abstract: Immunity against the pre-erythrocytic stages of malaria is the most promising, as it is strong and fully sterilizing. Yet, the underlying immune effectors against the human Plasmodium falciparum pre-erythrocytic stages remain surprisingly poorly known and have been little explored, which in turn prevents any rational vaccine progress. Evidence that has been gathered in vitro and in vivo, in higher primates and in humans, is reviewed here, emphasizing the significant role of IFN-γ, either as a critical immune m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…The study was conducted in Madibou, a semi-urban district located in a Southern part of Brazzaville [16], where malaria transmission is high and perennial with an entomological inoculation rate (EIR) of 22.5 infective bites/person/year estimated several years ago [17,18]. …”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in Madibou, a semi-urban district located in a Southern part of Brazzaville [16], where malaria transmission is high and perennial with an entomological inoculation rate (EIR) of 22.5 infective bites/person/year estimated several years ago [17,18]. …”
Section: Methodsmentioning
confidence: 99%
“…Although there are no established correlates of protective immunity against malaria, protection at the liver stage is thought to be mediated primarily by CD8 ϩ T cells, with a role for CD4 ϩ T cells, and production of Th1-type cytokines (13,67). IFN-␥ is routinely used as surrogate marker for preerythrocytic-stage immunity (72). Studies comparing malariaspecific cytokine profiles of protected and unprotected individuals and their capacity for inhibition of the development of early parasite stages confirmed the importance of IFN-␥ for protection but also established TNF as mediator of inhibition of preerythrocytic development (73)(74)(75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine preparation using human P.falciparun Liver Stage Antigen 3 (LSA-3) has demonstrated that Interferon-gamma (IFN-g) provided the protection experienced in the pre-eryhrocyctic stage, suggesting interaction between the LSA-3 peptide and the paratope that produced Interferongamma (IFN-g) [63]. Result shows AMA-1 0.4078 and Inferon gamma, 0.406.…”
Section: Liver Stage Antigen-3 (Lsa-3) and Inferon Gammamentioning
confidence: 98%
“…Clinical experiments have demonstrated that Inferon-gamma inhibit Liver Schizogony of the Plasmodium falciparun [63]. Vaccine preparation using human P.falciparun Liver Stage Antigen 3 (LSA-3) has demonstrated that Interferon-gamma (IFN-g) provided the protection experienced in the pre-eryhrocyctic stage, suggesting interaction between the LSA-3 peptide and the paratope that produced Interferongamma (IFN-g) [63].…”
Section: Liver Stage Antigen-3 (Lsa-3) and Inferon Gammamentioning
confidence: 99%
See 1 more Smart Citation